Preparation method of low-cost high-performance cu-cr composite contact material and cu-cr composite contact
Patent Information
- Application Number
- CN202611128447.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-23
AI Technical Summary
[0012]本发明提供一种低成本高性能CuCr复合触头材料的制备方法及CuCr复合触头,以解决现有技术中高性能工艺成本高昂、低成本工艺性能不足、梯度复合材料界面结合强度低以及液相烧结导致抗熔焊性下降等问题
1.本发明通过固相气压烧结技术,最终产品致密度高达98.5%以上,接近完全致密,带来了更好的导电性和抗烧蚀性。同时,固相烧结使得铜铬颗粒间的结合强度适度低于液相烧结。在电弧作用下,触头能更容易地从基体断开,而非焊接在一起,从而表现出优异的抗熔焊性。实验数据表明,采用本发明方法制备的CuCr复合触头抗熔焊性可达100次以上,远优于传统液相烧结工艺的60次左右。
Smart Images

Figure CN122955945A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrical materials technology, specifically to a method for preparing low-cost, high-performance CuCr composite contact materials and CuCr composite contacts. Background Technology
[0002] Copper-chromium contact material is a core component of medium- and high-voltage vacuum circuit breakers, requiring high conductivity, high resistance to arc erosion, and excellent resistance to welding. During operation, the contacts of a vacuum circuit breaker need to withstand short-circuit currents of up to several thousand amperes and arcs of tens of thousands of volts, thus placing extremely stringent requirements on the material properties.
[0003] The current mainstream preparation technologies mainly include the following: Vacuum infiltration is a method that infiltrates molten copper into a chromium skeleton or chromium powder compact under vacuum conditions to form a copper-chromium composite material. This method can produce high-density products (density can reach over 99%), but it has significant drawbacks: large equipment investment, requiring high-temperature smelting equipment; complex process, requiring precise control of infiltration temperature and time; limited furnace capacity, resulting in low production efficiency; and high cost, making it difficult to meet the needs of large-scale industrial production.
[0004] Hot isostatic pressing (HIP) processes apply high temperature and high pressure to powder compacts, achieving near-full densification of the material. While this method can produce high-performance copper-chromium contact materials, it also faces challenges such as huge equipment investment (high cost of HIP equipment), long process cycles, and high production costs, limiting its application in large-scale production.
[0005] Conventional molding-vacuum sintering technology has relatively low cost and requires minimal equipment investment, making it suitable for mass production. However, the materials produced by this process typically have a density of only 96%-97%, resulting in significant porosity and insufficient ablation resistance, thus affecting contact lifespan. Furthermore, single-component contacts cannot simultaneously meet the requirements of surface ablation resistance and high weld strength in the underlying layer.
[0006] In recent years, some improved technologies have been proposed, but each still has its own problems: Patent CN106710897A discloses a method for uniformly distributing remelted copper wire onto the contact surface using wire feeding printing technology, achieving a composite of copper-chromium contact material and pure copper. However, the drawback of this process is that the pure copper wire is cold-welded to the contact surface, resulting in low weld interface strength and easy delamination under the action of an electric arc.
[0007] Patent CN110504120A discloses a low-cost method for preparing copper-chromium composite contacts. The method involves first pre-pressing copper-chromium mixed powder in a mold, then filling pure copper powder into the pre-reserved space in the mold after pressing, performing a second pressing, followed by sintering and re-pressing / sintering. However, during the sintering process, due to the different shrinkage rates of pure copper and copper-chromium materials, the billet warps, causing deformation at the interface between the pure copper and copper-chromium contacts, resulting in a decrease in the overall performance of the composite material.
[0008] Patent CN111799116A discloses a method for spraying Cu and Cr powders onto the surface of a Cu plate under high temperature and pressure using a dual-gun cold spraying technique to form a blank. This method prepares copper-chromium composite contact materials through spraying. However, the interfacial bonding strength between the copper-chromium layer and the pure copper layer is low, and the copper-chromium layer is prone to peeling off when the sprayed layer is thick.
[0009] Patent CN121406929A discloses a method for preparing copper-based electrical contact gradient composite materials, employing a process of acoustic resonance powder mixing, molding, hydraulic sintering, and laser surface remelting. While this method can improve density, its process involves liquid-phase sintering, resulting in excessively high bonding strength between copper and chromium particles. Under the action of an electric arc, the contacts are difficult to separate from the matrix, weakening their resistance to welding.
[0010] In summary, the existing technologies have the following main problems: 1. High-performance processes (vacuum infiltration, hot isostatic pressing) are expensive and difficult to apply on a large scale; 2. Low-cost processes (ordinary vacuum sintering) have low density and insufficient performance; 3. Insufficient interfacial bonding strength or interfacial deformation during the preparation of gradient composite materials; 4. Liquid phase sintering leads to a decrease in resistance to welding; 5. The processes are complex, production efficiency is low, and material utilization is not high.
[0011] Therefore, there is an urgent need for a contact fabrication method that combines low cost, high density, high resistance to welding, and gradient functionalization to meet the demand for high-performance contact materials in medium and high voltage vacuum circuit breakers. Summary of the Invention
[0012] This invention provides a method for preparing low-cost, high-performance CuCr composite contact material and a CuCr composite contact, in order to solve the problems of high cost of high-performance processes, insufficient performance of low-cost processes, low interfacial bonding strength of gradient composite materials, and decreased resistance to fusion welding caused by liquid phase sintering in the prior art.
[0013] The technical solution provided by this invention is as follows: A method for preparing low-cost, high-performance CuCr composite contact materials includes the following steps: Ablative layer mixed powder and welding layer mixed powder are prepared separately. The ablative layer mixed powder contains 25%-50% chromium powder and 50%-75% copper powder by weight. The welding layer mixed powder contains 10%-25% chromium powder and 75%-90% copper powder by weight. The welding layer mixed powder and the ablation layer mixed powder are sequentially laid in a near-net-shape mold, and after laying, they are molded to obtain a composite blank. The composite preform was placed in a sintering furnace and evacuated to a vacuum of 5 × 10⁻⁶. -2 Below Pa, the temperature is raised in stages to 900-1020℃, and then argon gas is introduced into the furnace to make the gas pressure reach 6-12MPa. The temperature is held for 60-150 minutes and then cooled with the furnace to obtain the CuCr composite contact material.
[0014] Optionally, the segmented heating includes: Phase 1: Raise the temperature from room temperature to 400℃ at a rate of 2.0-3.0℃ / min, and hold at 400℃ for 40-60 minutes; Phase 2: Increase the temperature from 400℃ to 800℃ at a rate of 3.5-4.5℃ / min, and hold at 800℃ for 40-60 minutes; Phase 3: Raise the temperature from 800℃ to 900-1020℃ for 40-60 minutes to carry out solid-phase gas pressure sintering.
[0015] Optionally, the step of sequentially laying the weld layer mixed powder and the ablation layer mixed powder in a near-net-shape mold includes: The welding layer mixed powder and the ablation layer mixed powder are sequentially laid in a near-net-shape mold according to the blank thickness requirements; An extremely thin isolation layer is placed at the interface between the welding layer mixed powder and the ablation layer mixed powder, or a step-by-step pre-pressing technology is used for molding.
[0016] Optionally, the isolation layer is a nano-scale alumina coating; The step-by-step preloading technology includes: first preloading the bottom layer with 30-50 MPa, and then laying the top layer.
[0017] Optionally, the welding layer mixed powder and the ablation layer mixed powder are prepared by mixing copper powder and chromium powder according to the corresponding ratio of the welding layer mixed powder and the ablation layer mixed powder using a mixer. The mixer can be either a ball mill or a twin-roll screw press.
[0018] Optionally, the thickness of the ablation layer is 0.5-1.5 mm.
[0019] Optionally, the solid-state gas pressure sintering temperature is 950-1000℃; the argon pressure of the solid-state gas pressure sintering is 8-10MPa.
[0020] Optionally, the furnace-cooled process includes: controlling the depressurization rate to 10. -2 0 MPa / min, with the cooling rate controlled at 0.1-4.0℃ / min.
[0021] The present invention also provides a CuCr composite contact, which is prepared by the above-described preparation method.
[0022] Optionally, the CuCr composite contact has a relative density ≥98.5%, a hardness of 95-115HB, a weld resistance ≥100 times, and an electrical conductivity of 25-28MS / m.
[0023] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention utilizes solid-state gas pressure sintering technology, resulting in a final product with a density exceeding 98.5%, approaching complete densification, leading to improved conductivity and ablation resistance. Simultaneously, solid-state sintering results in a slightly lower bonding strength between copper-chromium particles compared to liquid-state sintering. Under the influence of an electric arc, the contacts can more easily detach from the substrate rather than be welded together, thus exhibiting excellent resistance to fusion welding. Experimental data shows that the CuCr composite contacts prepared using this method achieve a fusion welding resistance of over 100 cycles, far superior to the approximately 60 cycles achieved by traditional liquid-state sintering processes.
[0024] 2. Compared to hot isostatic pressing (HIP), this invention uses lower gas pressure, placing less emphasis on equipment and mold requirements, thus allowing for larger furnace loading and significantly reduced production costs. Compared to conventional vacuum sintering, the introduction of gas pressure greatly promotes the densification process, resulting in higher density and better performance in a shorter sintering time. Compared to high-temperature melting and infiltration (1450℃), this invention uses a lower sintering temperature (≤1020℃), reducing energy consumption and eliminating the need for copper melting and infiltration, thus achieving higher material utilization.
[0025] 3. A gradient green body is formed in one step through simple sequential powder spreading and molding, resulting in a simple and efficient process. Because the compositional differences between the upper and lower layers are minimal, the shrinkage coefficients are matched during sintering, effectively suppressing interface deformation and cracking, ensuring interface smoothness, and improving product yield. Near-net-shape molding eliminates subsequent machining steps, increasing material utilization and significantly reducing costs.
[0026] 4. This invention divides the contact into two layers, using different compositions for different functional requirements of different areas. The ablation layer (working surface): high chromium content (Cr 25%-50%) ensures excellent resistance to arc erosion and arc extinguishing capabilities. The welding layer (bonding surface): low chromium content (Cr 10%-25%) ensures high electrical and thermal conductivity as well as good welding performance with the base.
[0027] 5. The CuCr composite contact prepared by the method of the present invention has the following excellent properties: relative density ≥98.5%, hardness 95-115HB, resistance to welding: ≥100 times, electrical conductivity: 25-28MS / m. Attached Figure Description
[0028] Figure 1 A flowchart illustrating the preparation method of the low-cost, high-performance CuCr composite contact material provided by the present invention; Figure 2 This is a schematic diagram of the near-net-shape forming mold used in an embodiment of the present invention; Figure 3 This is a schematic diagram of gradient powder spreading and molding in an embodiment of the present invention; Figure 4 This is a temperature-pressure curve of the sintering process in an embodiment of the present invention; Figure 5 This is a metallographic photograph of the interface of the CuCr composite contact material prepared in Example 1 of the present invention. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the embodiments described below are only some embodiments of this application, and not all embodiments.
[0030] See Figure 1 This invention provides a method for preparing a low-cost, high-performance CuCr composite contact material, comprising the following steps: S1, Mixed Powder Ablative layer mixed powder and welding layer mixed powder were prepared separately. The weight percentage of chromium powder in the ablative layer mixed powder was 25%-50% and the weight percentage of copper powder was 50%-75%. The weight percentage of chromium powder in the welding layer mixed powder was 10%-25% and the weight percentage of copper powder was 75%-90%.
[0031] The ablation layer powder uses a high chromium content (25%-50%). Chromium has a high melting point (approximately 1900℃) and good resistance to arc erosion, effectively resisting high-temperature arc erosion and extending the contact life. The welding layer powder uses a low chromium content (10%-25%) to ensure excellent electrical and thermal conductivity, while also providing good weldability to the base.
[0032] S2, Compression molding The welding layer mixed powder and the ablation layer mixed powder are sequentially laid in a near-net-shape mold, and after laying, they are molded to obtain a composite blank.
[0033] Specifically, this step employs near-net-shape forming technology for compression molding. Near-net-shape forming uses a mold with dimensions identical to the contact's outer shape to press the contact into place in one step, eliminating subsequent machining processes. This results in high material utilization, a short preparation process, and lower costs. The gradient powder spreading process forms a gradient preform in one step through simple sequential powder spreading and molding, making the process simple and efficient. Because the compositional differences between the upper and lower layers are minimal, the shrinkage coefficients match during sintering, effectively suppressing interface deformation and cracking, ensuring interface smoothness, and improving product yield.
[0034] S3, Solid-state gas pressure sintering The composite green body was placed in a sintering furnace and evacuated to a vacuum level of 5×10⁻⁶. -2 Below Pa, the temperature is raised in stages to 900-1020℃, and then argon gas is introduced into the furnace to make the gas pressure reach 6-12MPa. The furnace is held at this temperature and pressure for 60-150 minutes and then cooled with the furnace to obtain CuCr composite contact material.
[0035] Solid-state pressure sintering is one of the core innovations of this invention. At temperatures far below the melting point of copper (900-1020℃), high-pressure argon gas (6-12 MPa) is applied to promote diffusion and densification between powder particles. This is solid-state sintering, which is fundamental to achieving subsequent performance advantages. The high-pressure gas provides a tremendous sintering driving force, forcing the powder particles to undergo plastic flow and grain boundary diffusion, compensating for the insufficient diffusion motive power in solid-state sintering.
[0036] This invention utilizes solid-state pressure sintering technology, resulting in a final product with a density exceeding 98.5%, approaching complete densification, leading to improved conductivity and ablation resistance. Simultaneously, solid-state sintering results in a slightly lower bonding strength between copper-chromium particles compared to liquid-phase sintering. Under the influence of an electric arc, the contacts can more easily detach from the substrate rather than be welded together, thus exhibiting excellent resistance to fusion welding. Experimental data shows that the CuCr composite contacts prepared using this method achieve a fusion welding resistance of over 100 cycles, far superior to the approximately 60 cycles achieved by traditional liquid-phase sintering processes.
[0037] like Figure 2 As shown, the near-net-shape forming mold used in step S2 includes an upper punch, a lower punch, a middle mold, and a core mold. The petal structure of the middle mold can be machined as a single piece or assembled separately to adapt to different contact shapes. The inner walls of the upper punch, lower punch, and middle mold are all plated with carbon nitride, chromium nitride, or rose gold wear-resistant coatings, which are resistant to powder wear and do not easily stick to powder during the pressing process, ensuring the surface smoothness of the blank. The core rod passes through the center of the mold and is used to form the central assembly hole of the contact, realizing the forming of the inner and outer contours in one pressing. The dimensions of the entire mold are matched with the finished contact, and the near-net-shape forming design is adopted. After pressing, the shape, hole diameter, and thickness of the composite blank do not require secondary machining, which greatly improves the material utilization rate. When layering powder, the mold cavity has good sealing performance, which can accurately control the powder filling amount of the welding layer and ablation layer, avoid powder leakage, and adapt to the gradient double-layer powder step-by-step pre-pressing or direct molding process, reducing interface mixing defects.
[0038] In step S2, the amount of powder used in the compression molding is calculated based on the required compression density and thickness: mablation layer = ρablation layer density × Vablation layer volume m_weld layer = ρ_weld layer density × V_weld layer volume Among them, ρ ablation layer density and V ablation layer volume refer to the density and volume of the ablation layer corresponding to the final product drawing; ρ weld layer density and V weld layer volume refer to the density and volume of the weld layer corresponding to the final product drawing; and m ablation layer and m weld layer refer to the final powder loading of the ablation layer mixed powder and the weld layer mixed powder.
[0039] In other embodiments, step S3, the segmented heating process may include: Phase 1: Raise the temperature from room temperature to 400℃ at a rate of 2.0-3.0℃ / min, and hold at 400℃ for 40-60 minutes.
[0040] Phase 2: Increase the temperature from 400℃ to 800℃ at a rate of 3.5-4.5℃ / min, and hold at 800℃ for 40-60 minutes.
[0041] Phase 3: Raise the temperature from 800℃ to 900-1020℃ for 40-60 minutes to carry out solid-phase gas pressure sintering.
[0042] When the temperature reaches 900-1020℃, high-purity argon gas is introduced into the furnace to make the gas pressure reach 6-12MPa. The furnace is then held at this pressure and temperature for 60-150 minutes. The high-pressure gas provides a huge sintering driving force, forcing the powder particles to undergo plastic flow and grain boundary diffusion, thus compensating for the lack of diffusion power in solid-phase sintering.
[0043] The temperature-pressure curve of the sintering process in step S2 of this invention is shown in the figure below. Figure 4 As shown.
[0044] The segmented heating process used in this embodiment ensures that the lubricant is fully removed and the composite green body is heated evenly, avoiding cracking or performance degradation of the green body due to excessively rapid heating. Holding at 400℃ can fully remove the lubricant, holding at 800℃ promotes the initial diffusion between powder particles, and finally heating to the solid-state sintering temperature for densification.
[0045] In other embodiments, the welding layer mixed powder and the ablation layer mixed powder are sequentially laid in a near-net-shape mold, including: the welding layer mixed powder and the ablation layer mixed powder are sequentially laid in a near-net-shape mold according to the blank thickness requirements; By setting an extremely thin isolation layer at the interface between the welding layer mixed powder and the ablation layer mixed powder, or by using a step-by-step pre-pressing technology for molding, interlayer diffusion mixing can be prevented.
[0046] Specifically, during powder application, the amount of powder to be filled in the two layers is strictly calculated based on the target blank thickness. First, the welding layer mixed powder is filled, followed by the ablation layer mixed powder. The layering order is fixed, matching the functional zones of the bottom welding layer and the surface arc-resistant layer of the contact. To prevent mixing between the two powder layers during filling and pressing, two mixing control schemes are implemented: First, a thin nano-alumina insulating layer is coated at the interface of the two powder layers. This thin film blocks the cross-layer penetration of copper and chromium particles, and the trace amount after sintering does not affect the interface bonding strength. Second, a step-by-step pre-pressing process is adopted. First, the welding layer powder is filled into the mold, and a pressure of 30–50 MPa is applied for pre-pressing to compact it and fix the shape of the bottom powder layer. Then, the ablation layer mixed powder is laid to complete the overall molding. Both methods can prevent interlayer powder mixing, ensure precise stratification of the gradient components, match the shrinkage rates of the two layers during sintering, and result in a smooth and distortion-free interface, stabilizing the contact's conductivity and ablation resistance.
[0047] In other embodiments, the insulating layer is a nano-scale alumina coating. The step-by-step preloading technique includes: first preloading the bottom layer with 30-50 MPa, and then laying the top layer.
[0048] The powder spreading method and molding diagram used in step S2 are shown below. Figure 3 As shown. Figure 3This visually demonstrates the stress and layered structure of double-layer gradient powder molding. The mold cavity is filled from bottom to top with a mixture of Cr10%-25% welding layer powder and Cr25%-50% ablation layer powder. Bidirectional pressure F is applied from both the top and bottom punches to complete the overall molding. The bottom welding layer serves as the contact welding interface, while the surface ablation layer is the arc working surface. The composition gradient between the two layers is gentle, and the sintering shrinkage coefficients are matched, effectively avoiding interface warping and cracking. Two layer control processes can be used: one is to spray a nano-alumina isolation layer between the layers to prevent powder mixing; the other is to pre-press the bottom welding layer at 30-50MPa, then apply the ablation layer and apply secondary pressure. The bidirectional isostatic pressing method ensures uniform internal density of the blank, eliminating density differences between the upper and lower layers. Combined with a near-net-shape molding cavity, the ablation layer thickness can be precisely controlled at 0.5-1.5mm. After molding, the interlayer interfaces of the composite blank are smooth, providing a defect-free blank for subsequent solid-state gas pressure sintering and significantly improving the yield of finished products.
[0049] In other embodiments, the preparation method of the welding layer mixed powder and the ablation layer mixed powder is as follows: copper powder and chromium powder are mixed according to the corresponding ratio of welding layer mixed powder and ablation layer mixed powder using a mixer. The mixer can be either a ball mill or a twin-roll screw press.
[0050] In other embodiments, the thickness of the ablation layer is 0.5-1.5 mm. The design of the ablation layer thickness needs to take into account both ablation resistance and cost; a thickness of 0.5-1.5 mm can ensure sufficient ablation resistance without excessively increasing costs.
[0051] In other embodiments, the solid-state pressure sintering temperature is 950-1000℃, which is the optimal temperature range for solid-state pressure sintering, ensuring sufficient diffusion driving force while avoiding entry into the liquid phase region.
[0052] The argon pressure in solid-state gas pressure sintering is 8-10 MPa. An argon pressure of 8-10 MPa can provide sufficient sintering driving force to promote densification, while the equipment requirements are relatively relaxed.
[0053] In other embodiments, the furnace-cooled process includes controlling the pressure relief rate at 10-20 MPa / min and the cooling rate at 0.1-4.0 °C / min. Controlling the cooling rate can prevent material cracking due to excessive thermal stress while ensuring material performance.
[0054] The present invention also provides a CuCr composite contact, which is prepared by the above-described preparation method.
[0055] As a further improvement to the CuCr composite contact of this invention, the CuCr composite contact has a relative density ≥98.5%, a hardness of 95-115 HB, a weld resistance ≥100 cycles, and an electrical conductivity of 25-28 MS / m. These performance indicators demonstrate that the CuCr composite contact prepared by this invention possesses excellent comprehensive performance. All of the above performance indicators meet or exceed those of products prepared using existing high-performance processes, while significantly reducing production costs.
[0056] Example 1 This embodiment provides a method for preparing a low-cost, high-performance CuCr composite contact material, including the following steps: S1, Mixed Powder Separate ablation layer mixed powder and welding layer mixed powder were prepared. The weight percentage of chromium powder in the ablation layer mixed powder was 35% and that of copper powder was 65%; the weight percentage of chromium powder in the welding layer mixed powder was 18% and that of copper powder was 82%. The materials were mixed using a ball mill for 4 hours at a speed of 200 rpm.
[0057] S2, Compression molding The welding layer mixed powder and the ablation layer mixed powder are sequentially laid in a near-net-shape mold. The ablation layer thickness is designed to be 1.0 mm, and the welding layer thickness is determined based on the total contact thickness. After laying, compression molding is performed at a pressure of 400 MPa and a holding time of 30 seconds to obtain a composite preform.
[0058] S3, Solid-state gas pressure sintering The composite green body was placed in a sintering furnace and evacuated to a vacuum level of 5×10⁻⁶. -2 Pa, then increase the temperature in stages according to the following procedure: Stage 1: Increase the temperature from room temperature to 400℃ at a rate of 2.67℃ / min (total duration 150min), and hold at 400℃ for 50min to fully remove the lubricant; Stage 2: Increase the temperature from 400℃ to 800℃ at a rate of 4℃ / min (total duration 100min), and hold at 800℃ for 50min to promote initial diffusion between powder particles; Stage 3: Increase the temperature from 800℃ to 980℃ for 50min.
[0059] When the temperature reaches 980℃, high-purity argon gas is introduced into the furnace to achieve a gas pressure of 10MPa. The furnace is then held at this pressure and temperature for 120 minutes. The high-pressure gas provides a tremendous driving force for sintering, forcing the powder particles to undergo plastic flow and grain boundary diffusion, thereby achieving densification.
[0060] After the heat preservation is completed, the pressure relief rate is controlled at 15 MPa / min, the cooling rate is controlled at 2℃ / min, and the material is cooled to room temperature with the furnace to obtain CuCr composite contact material.
[0061] The performance of the CuCr composite contact material prepared in this embodiment was tested, and the results are as follows: It has a relative density of 98.8%, a hardness of 105HB, a weldability of >100 times, and an electrical conductivity of 26.5MS / m.
[0062] Metallographic images of the interface of the CuCr composite contact material prepared in this embodiment are shown below. Figure 5 As shown, Figure 5 The image shows a metallographic micrograph of the interlayer interface of the gradient CuCr composite contact prepared in Example 1 of this invention. The scale bar is 100 μm. The light copper-colored matrix in the image represents the copper phase, and the dark gray blocky particles represent the chromium phase, clearly showing the interface between the two gradient materials. The overall interface is continuous and smooth, without obvious cracks, pores, delamination, or large-area elemental mixing defects, proving that the layered powder spreading combined with the isolation / stepwise pre-pressing process effectively suppresses interlayer powder mixing. After solid-phase gas pressure sintering, the copper and chromium particles diffuse and bond appropriately, without the excessive fusion phenomenon caused by liquid-phase sintering. The low-chromium particles in the welding layer are evenly distributed, ensuring conductivity and welding performance; the high-chromium particles in the ablation layer have a higher proportion, giving the contact excellent arc erosion resistance. The metallographic structure directly verifies that the gradient forming and solid-phase sintering process of this invention can obtain a composite contact matrix with a complete structure and clear compositional partitioning.
[0063] Example 2 This embodiment provides a method for preparing a low-cost, high-performance CuCr composite contact material, which is basically the same as that in Embodiment 1, except that: The ablation layer mixed powder contains 45% chromium powder and 55% copper powder by weight; the weld layer mixed powder contains 15% chromium powder and 85% copper powder by weight.
[0064] The solid-state gas pressure sintering temperature is 1000℃, the argon pressure is 8MPa, and the holding time is 150 minutes.
[0065] The performance of the CuCr composite contact material prepared in this embodiment was tested, and the results are as follows: It has a relative density of 98.6%, a hardness of 110HB, a weldability of >100 times, and an electrical conductivity of 25.8MS / m.
[0066] Example 3 This embodiment provides a method for preparing a low-cost, high-performance CuCr composite contact material, which is basically the same as that in Embodiment 1, except that: The ablation layer mixed powder contains 25% chromium powder and 75% copper powder by weight; the weld layer mixed powder contains 25% chromium powder and 75% copper powder by weight.
[0067] The solid-state gas pressure sintering temperature is 950℃, the argon pressure is 12MPa, and the holding time is 60 minutes.
[0068] A nano-scale alumina coating is provided at the interface of the two powder layers as an isolation layer to prevent interlayer diffusion and mixing.
[0069] The performance of the CuCr composite contact material prepared in this embodiment was tested, and the results are as follows: It has a relative density of 98.5%, a hardness of 98HB, a weldability of >100 times, and an electrical conductivity of 27.2 MS / m.
[0070] Comparative Example 1 The same powder ratio and molding process as in Example 1 were used, but a conventional vacuum sintering process was adopted, that is, sintering at 980°C under vacuum (0MPa) for 120 minutes.
[0071] The performance test results of the CuCr composite contact material prepared in Comparative Example 1 are as follows: It has a relative density of 96.5%, a hardness of 98HB, a weld resistance of 85 times, and an electrical conductivity of 24.0 MS / m.
[0072] Compared to Example 1, Comparative Example 1 exhibits significantly lower density, poorer weldability, and lower electrical conductivity. This indicates that conventional vacuum sintering, lacking pressure drive, results in insufficient densification, leading to a decline in material properties.
[0073] Comparative Example 2 CuCr composite contact material was prepared using a traditional high-temperature melting and infiltration process, which included preparing a chromium skeleton compact and then performing copper melting and infiltration at 1450℃ for 60 minutes.
[0074] The performance test results of the CuCr composite contact material prepared in Comparative Example 2 are as follows: It has a relative density of 99.2%, a hardness of 120HB, a weldability of 60 cycles, and an electrical conductivity of 22.1MS / m.
[0075] Compared to Example 1, Comparative Example 2, while having a higher density, also had a higher hardness and a drastically reduced resistance to welding (only 60 cycles). This is because high-temperature infiltration involves liquid-phase sintering, resulting in excessively high bonding strength between the copper and chromium particles, making it difficult for the contacts to detach from the substrate under the action of an electric arc. Furthermore, the high-temperature infiltration process is energy-intensive and costly.
[0076] Performance Comparison Analysis The table below summarizes the performance comparison between the embodiments of the present invention and the comparative examples:
[0077] As can be seen from the table: 1. Increased density: Compared with Comparative Example 1 (vacuum sintering), this invention uses high-pressure gas pressure sintering, which increases the density from 96.5% to over 98.5%, approaching full density, thus solving the problem of low density in ordinary molding sintering.
[0078] 2. Balance of resistance to fusion welding: Compared to Comparative Example 2 (high-temperature melting and infiltration), although Comparative Example 2 has a higher density, the high temperature leads to coarse grains and increased hardness (120HB), resulting in a sharp decrease in resistance to fusion welding (only 60 times). The present invention sintersulates at a solid-state temperature, preserving the hardness and strength of the material, and its resistance to fusion welding is far superior to that of Comparative Example 2.
[0079] 3. Cost advantage: Compared with the high temperature of 1450℃ infiltration in Comparative Example 2, the sintering temperature of this invention is low (≤1020℃), energy consumption is reduced, and there is no need for copper infiltration, resulting in high material utilization.
[0080] 4. Excellent overall performance: The CuCr composite contact prepared by this invention exhibits excellent overall performance in terms of density, hardness, weldability and conductivity, which fully meets the requirements of medium and high voltage vacuum circuit breakers for contact materials.
[0081] This invention optimizes key process parameters through extensive experimentation: 1. Sintering temperature Sintering temperature is a key parameter affecting density and performance. Experiments show that when the sintering temperature is below 900℃, the diffusion driving force is insufficient, making it difficult to achieve a density of over 98.5%; when the sintering temperature is above 1020℃, it approaches the melting point of copper (1083℃), which may lead to the formation of localized liquid phases, resulting in decreased resistance to welding. Therefore, the preferred sintering temperature range is 900-1020℃, more preferably 950-1000℃.
[0082] 2. Gas pressure Gas pressure is a key factor in promoting densification. Experiments show that when the gas pressure is below 6 MPa, the sintering driving force is insufficient, resulting in limited density improvement; when the gas pressure is above 12 MPa, the equipment requirements are too high, increasing costs, while the density improvement is limited. Therefore, the preferred gas pressure range is 6-12 MPa, more preferably 8-10 MPa.
[0083] 3. Insulation time The holding time affects the degree of densification and grain size. Experiments show that when the holding time is less than 60 minutes, densification is insufficient; when the holding time is longer than 150 minutes, grains grow, hardness increases, and resistance to welding decreases. Therefore, the preferred holding time range is 60-150 minutes.
[0084] 4. Ingredient Design The ablation layer has a chromium content ranging from 25% to 50%, ensuring excellent ablation resistance; the weld layer has a chromium content ranging from 10% to 25%, ensuring good electrical and thermal conductivity and weldability. This compositional gradient design allows the contacts to simultaneously meet the functional requirements of different areas.
[0085] The low-cost, high-performance CuCr composite contact material prepared by this invention can be widely used in electrical equipment such as medium and high voltage vacuum circuit breakers, vacuum contactors, and vacuum load switches, and has broad application prospects. Compared with existing technologies, this invention significantly reduces production costs while ensuring high performance, resulting in significant economic and social benefits.
[0086] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing low-cost, high-performance CuCr composite contact material, characterized in that, Includes the following steps: Ablative layer mixed powder and welding layer mixed powder are prepared separately. The ablative layer mixed powder contains 25%-50% chromium powder and 50%-75% copper powder by weight. The welding layer mixed powder contains 10%-25% chromium powder and 75%-90% copper powder by weight. The welding layer mixed powder and the ablation layer mixed powder are sequentially laid in a near-net-shape mold, and after laying, they are molded to obtain a composite blank. The composite preform was placed in a sintering furnace and evacuated to a vacuum of 5 × 10⁻⁶. -2 Below Pa, the temperature is raised in stages to 900-1020℃, and then argon gas is introduced into the furnace to make the gas pressure reach 6-12MPa. The temperature is held for 60-150 minutes and then cooled with the furnace to obtain the CuCr composite contact material.
2. The preparation method according to claim 1, characterized in that, The segmented heating includes: Phase 1: Raise the temperature from room temperature to 400℃ at a rate of 2.0-3.0℃ / min, and hold at 400℃ for 40-60 minutes; Phase 2: Increase the temperature from 400℃ to 800℃ at a rate of 3.5-4.5℃ / min, and hold at 800℃ for 40-60 minutes; Phase 3: Raise the temperature from 800℃ to 900-1020℃ for 40-60 minutes to carry out solid-phase gas pressure sintering.
3. The preparation method according to claim 1, characterized in that, The step of sequentially laying the welding layer mixed powder and the ablation layer mixed powder in a near-net-shape mold includes: The welding layer mixed powder and the ablation layer mixed powder are sequentially laid in a near-net-shape mold according to the blank thickness requirements; An extremely thin isolation layer is placed at the interface between the welding layer mixed powder and the ablation layer mixed powder, or a step-by-step pre-pressing technology is used for molding.
4. The preparation method according to claim 3, characterized in that, The isolation layer is a nano-scale alumina coating; The step-by-step preloading technology includes: first preloading the bottom layer with 30-50 MPa, and then laying the top layer.
5. The preparation method according to claim 1, characterized in that, The preparation method of the welding layer mixed powder and the ablation layer mixed powder is as follows: copper powder and chromium powder are mixed according to the corresponding ratio of the welding layer mixed powder and the ablation layer mixed powder using a mixer. The mixer can be either a ball mill or a twin-roll screw mill.
6. The preparation method according to claim 1, characterized in that, The thickness of the ablation layer is 0.5-1.5 mm.
7. The preparation method according to claim 2, characterized in that, The solid-state gas pressure sintering temperature is 950-1000℃; the argon pressure of the solid-state gas pressure sintering is 8-10MPa.
8. The preparation method according to claim 1, characterized in that, The furnace-cooled process includes: controlling the depressurization rate to 10. -2 0 MPa / min, with the cooling rate controlled at 0.1-4.0℃ / min.
9. A CuCr composite contact, characterized in that, The CuCr composite contact is prepared by the preparation method described in any one of claims 1-8.
10. The CuCr composite contact according to claim 9, characterized in that, The CuCr composite contact has a relative density of ≥98.5%, a hardness of 95-115HB, a weld resistance of ≥100 cycles, and an electrical conductivity of 25-28MS / m.
Citation Information
Patent Citations
Preparation method of copper-chromium composite contact
CN106710897A
Low-cost copper-chromium composite contact terminal preparation method
CN110504120A
Preparation method of rapidly-formed copper-chromium composite contact
CN111799116A
Preparation method of copper-based electric contact gradient composite material
CN121406929A